Sumber-Sumber Penafsiran Al-Quran - Muhammad Zaini (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2012)
Interpretation is human effort to explore their highest ability to understand the scare text as meant by the Owner of the text. The effort is not easy, indeed. Because every written or spoken word is only well understood by the owner. Thus, the truth resulted from any interpretation is not absolute. For this purpose, interpreter of Qur-an take particular methodologies to interpret the scare book, especially in determining source or references that they will use for interpretation. The variety of methodology can be seen from the interpretation they resulted.